Da vontade desesperada em querer tornar-se si mesmo à tristeza de nunca sermos dois: a questão do eu em Kierkegaard e Mário de Sá-Carneiro. - SOUSA, Leonardo Silva (2017)
This research aims to gather Soren Aabye Kierkegaard (1813 – 1855) phylosophy to the portuguese poet Mário de Sá Carneiro (1890 – 1916) through a theme that is developed in the authors’ works: the matter of myself. Kierkegaard develops this theme starting from the conception that man is a synthesis between heterogeneous elements – the finite and the infinite, the temporal and the eternal, the possibility and the necessity. In his literature, Sá-Carneiro deals with this issue presenting a subject in phycho disorder, characterized as a fragmented being, unable to balance personal desires and goals with reality. Although they develop this problem in different way in their works, we sustain the following hypothesis: both in Kierkegaard and in Sá-Carneiro we noticed the human being existing problem while looking for fufillments that may eliminate the incompleteness experience which lies inside the subject. To fight the problem of synthesis, facing despair, man must become him himself, with faith helping him trying to eliminate the mortal illness. In Mário de Sá Carneiro, there is a recurrence to the double, when the subject spreads trying to reach the accomplishment of something, harmonizing imagination and reality. The present paper aims to present how the authors develop this theme. To the development of the problem, we take as main works the texts Fear and fright (1843) and Human despair (1849), from the danish phylosopher and the novel Lucio’s confession (1913), from the portuguese writer. Lately, the work moves towards an interpretation of the short story “The man of the dreams”, from Sá-Carneiro, considering the aesthetic stage as the reading key to the text. In this analysis stage, we seek to find similarities between the character named Russo in Sá Carneiro’s short story, and Johannes, pseudonym and author of Diary of a seducer (1843), which lives this existence possibility. At last, we analyse two characters from Lucio’s confession still by the existence aesthetic stage perspective.